Complexities and Challenges in the Implementation of Green Accounting - Rao Badia, Venkat; Suryanarayana, A.; Ravi, Aluvala (Jurnal Dinamika Ekonomi dan Bisnis, 2025)
The heightened urgency around environmental protection and climate action has thrust the issue of corporate sustainability into the global spotlight. Shareholders, regulators, consumers, and other stakeholders are increasingly demanding that businesses take concrete steps to measure, manage, and mitigate their environmental impacts. “Green Accounting” has emerged as a powerful tool to help organizations meet these expectations and demonstrate their commitment to sustainability. It is also known as environmental accounting or ecological accounting and acts as a critical tool for organizations to measure, record, and report their environmental impacts and sustainability efforts. As the global community becomes increasingly aware of the pressing need to address climate change and environmental degradation, there is a growing emphasis on corporate accountability and transparency when it comes to environmental performance. Green Accounting provides a structured framework for companies to track and communicate their use of natural resources, greenhouse gas emissions, waste generation, and other environmentally-relevant metrics. It refers to the systematic identification, collection, analysis, and communication of information about a company's interactions with the natural environment. This includes tracking the consumption of natural resources, emissions of pollutants and greenhouse gases, waste generation, and other environmentally-relevant metrics. The ultimate goal is to provide decision-makers - both internal and external to the organization - with accurate, comprehensive data to inform strategic planning, investment decisions, and public reporting. This Conceptual Paper makes an attempt to outline the importance of Green Accounting and explore the growing adoption and implications of this practice for organizations operating in the international business landscape.  This exploration of the challenges, research gaps, and future directions seeks to provide a deeper understanding of how organizations can effectively incorporate environmental considerations into their financial frameworks, fostering long-term sustainability and corporate responsibility.